GPR survey in the Taquari River, Pantanal Wetland, west-central Brazil - Porsani, Jorge Luís; Moutinho, Leandro; Assine, Mario Luis [UNESP] (My University, 2004)
A pioneer GPR - Ground Penetrating Radar - survey was carried out in the Pantanal of Mato Grosso State, westcentral region of Brazil. Fieldwork acquisitions were carried out in February/2001 and August/2002 in order to understand avulsion processes that are occurring within the Taquari alluvial megafan. The main subjects were to map channel, crevasses and floodplain morphology, as well as active sedimentary bedforms. Many GPR profiles were surveyed in the medium and lower Taquari River course. Subaqueous megaripples and exposed sand bars inside the Taquari channel were identified in the medium fan area. Similar features were observed in the lower fan channels, where there are also many crevasses in the marginal levees. During the flooding seasons the flow splays out in the floodplain where new distributary channels are being formed. As shown by GPR data, in the lower fan the Taquari channel is topographically higher than the adjacent floodplain, situation in which avulsion is a natural process of river course shifting. The lack of information about river morphology and dynamics is a major strain to better understand the sediment transport and the avulsion processes in the Taquari megafan. In this context, the GPR data obtained in wet and dry seasons, integrated to sedimentological information, have been very important to characterize the fluvial dynamics and the avulsion phenomena.
Keywords: Brazil; Fluvial avulsion; GPR; Pantanal basin; Taquari River; Floods; Flow of water; Geological surveys; Geomorphology; Rivers; Sediment transport; Sedimentology; Wetlands; Floodplains; Pantanal basin, Brazil; Taquari River, Brazil; Ground penetrating radar systems